2018
DOI: 10.2478/enr-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short- and long-term regular exercise on reproductive tissue in streptozotocin-induced diabetic male Wistar rats

Abstract: Objective. Reproductive disorders are one of the complications of diabetes mellitus. Since conflicting results have been obtained from different studies, which examined serum levels of cytokines in patients with diabetes, and considering the fact that the origin of cytokines cannot be accurately determined from their serum changes, attempts were made in the present study to study histological changes and testicular tissue levels of TNF-α and IL-1 in rats treated with exercise. Considering the effects of exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Notably, it has been reported that the impairment of the sperm parameters in obese and diabetes models is associated with inflammatory reactions (Wang et al 2018), which play an important role in male infertility (Mogaddami et al 2018). In this model, MetS led to inflammatory responses in the testis involving increase of expression IL-6R mRNA and IL-1R mRNA (the receptors of IL-1 and IL-6 pro-inflammatory cytokines).…”
Section: Discussionmentioning
confidence: 86%
“…Notably, it has been reported that the impairment of the sperm parameters in obese and diabetes models is associated with inflammatory reactions (Wang et al 2018), which play an important role in male infertility (Mogaddami et al 2018). In this model, MetS led to inflammatory responses in the testis involving increase of expression IL-6R mRNA and IL-1R mRNA (the receptors of IL-1 and IL-6 pro-inflammatory cytokines).…”
Section: Discussionmentioning
confidence: 86%
“…Mogaddami et al reported a positive effect of exercise in reducing blood sugar levels and increasing the number of primary spermatocytes in SZID rats. Exercise also ameliorated diabetes induced endothelium damage, which results in decreased vessel epithelium thickness (Mogaddami et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the spatial maps that testis produced in normal and diabetic mice revealed the destruction of the spatial cells and tissues of spermatogenic tubules in diabetic mice, resulting in spermatogenic disorders (Chen et al 2021 ). In addition, diabetes can also cause histological changes in testicular veins and the diameter of sertoil cells, resulting in decreased tissue perfusion and affecting testicular function (Mogaddami et al 2018 ). The mechanism of testicular dysfunction is closely related to the above complex pathophysiological changes in diabetes.…”
Section: Potential Mechanism Of Male Infertility Induced By Diabetesmentioning
confidence: 99%
“…In addition, animal experiments have shown that diabetes often causes histological changes in the male reproductive system, especially changes in the diameter of testicular veins and sertoil cells and the thickness of convoluted seminiferous tubules, leading to tissue perfusion abnormalities of reproductive organs. Short and long-term regular exercise can improve the adverse changes in these histologies to restore normal tissue perfusion and effectively improve reproductive disorders (Mogaddami et al 2018 ). A related systematic review and meta-analysis showed that combined aerobic and resistance training (CET) appears to be the best form of exercise for improving male fertility, but its overall efficacy remains controversial (Hajizadeh Maleki et al 2022 ).…”
Section: Potential Therapeutic Measures For Diabetes-induced Male Inf...mentioning
confidence: 99%